Assessment by proxy of the SF-36 and WHO-DAS 2.0. A systematic review - Juan David Hernández; María Alejandra Spir; Kelly Payares; Ana Maria Posada; Fabio Alonso Salinas; Héctor Iván Garcia; Luz H. Lugo-Agudelo (Medical Journals Sweden, 2023)
Background and objective: In some cases, for the evaluation of the health status of patients it is not possible to obtain data directly from the patient. The objective of this study was to determine if the instruments that cannot be applied to the patient can be completed by a proxy. Methods: A systematic review of the literature was carried out and 20 studies were included. The instruments reviewed in this synthesis were: Short Form-36 (SF-36), Montreal Cognitive Assessment (MoCA), WHODAS 2.0, Patient Health Questionnaire 9 (PHQ-9), State-Trait Anxiety Inventory (STAI), Disability Rating Scale (DRS). Results: The levels of agreement between the responses of the patients and the proxies were good, mainly when evaluating HRQoL and functioning with the SF-36 and WHODAS 2.0 instruments, respectively, with a higher level of agreement in the more objective and observable domains such as physical functioning and lower level of agreement in less objective domains, such as emotional or affective status, and self-perception. Conclusion: In patients who cannot complete the different instruments, the use of a proxy can help avoid the omission of responses. LAY ABSTRACT People with certain mental or neurological illnesses are often unable to answer questions about their health sta-tus, functional ability, or quality of life. In some cases, a relative or a person who knows the patient can fill out questionnaires to find out how affected he/she is, detect changes in his/her condition and even evaluate the response to the interventions performed. These people are known as proxies. This research sought to assess which questionnaires for measuring depression, anxiety, neurocognitive impairment, quality of life, function, or disability can be answered by a proxy, when patients cannot answer for themselves. For this, the medical literature published on this subject was reviewed. Twenty studies showing a good agreement between the responses of the patients and the proxies were found, especially in the assessment of quality of life and functional capacity. The use of a proxy can help avoid the omission of responses.